Mental health actions and nurse's work - Janaína Cristina Pasquini de Almeida; Celma Aparecida Barbosa; Letícia Yamawaka de Almeida; Jaqueline Lemos de Oliveira; Jacqueline de Souza (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to analyze the perception of nurses and other members of the patient care team about nurses' actions in mental health care. Methods: the study was conducted with professionals from mental health services in the interior of the state of São Paulo. The data collected through semi-structured interviews, a questionnaire with closed questions and a focus group were submitted to content analysis. Results: the participants referred mainly to the nursing care with the body and physical health, but also identified the nurse as a "gateway" for care, facilitator and integrator of actions and as the professional who has more contact with the user. Final considerations: although the stereotype of nursing as "body caregiver" refers to the beginnings of psychiatric nursing, the perception of the participants showed aspects that suggest a change in relation to the role traditionally attributed to this profession.